Non-Linear Development of Society and Nоn-Economic Capital - L. N. Fedotov (Vestnik MGIMO-Universiteta, 2013)
The paper focuses on nonlinear sociocultural dynamics inherent in a number of modern development processes. New approaches which reject the linear interpretation of social development and take into account its complexity and risks are discussed in the paper. The author analyses the types of non-economic capital (human, intellectual, social, cultural, sembolic and environmental) and their influence on the processes of the development and modernization.